1990
DOI: 10.1177/0145482x9008401013
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Use of Assistive Technology with Children: A Survey

Abstract: This article reports on the responses of 120 teachers and habilitative specialists of multiply handicapped blind and deaf-blind children in Massachusetts to a survey on their use of assistive technology. The respondents reported problems in all areas covered by the survey: knowledge of electronic mobility aids and communication devices; the availability, maintenance, and funding of devices; and adequate information about devices. They especially mentioned the need for resources to assess and match stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…As the literature illustrates, the nonuse of assistive technology by students could be attributed, in part, to the inadequate knowledge and skills of teachers of students with visual impairments in this area (Lee & Vega, 2005). In their pioneering investigation, Parker et al (1990) revealed that almost two-thirds of the teachers of students with visual impairments in their study thought of themselves as having "poor" or "nonexistent" knowledge of specific assistive technology devices. Edwards and Lewis (1998) also noted that the participating teachers in their Florida study did not use many of the listed assistive technology devices because they did not have knowledge of these devices.…”
mentioning
confidence: 99%
“…As the literature illustrates, the nonuse of assistive technology by students could be attributed, in part, to the inadequate knowledge and skills of teachers of students with visual impairments in this area (Lee & Vega, 2005). In their pioneering investigation, Parker et al (1990) revealed that almost two-thirds of the teachers of students with visual impairments in their study thought of themselves as having "poor" or "nonexistent" knowledge of specific assistive technology devices. Edwards and Lewis (1998) also noted that the participating teachers in their Florida study did not use many of the listed assistive technology devices because they did not have knowledge of these devices.…”
mentioning
confidence: 99%
“…What are the barriers that hinder the use of assistive technology by students who are visually impaired? Mounting evidence has attributed this nonuse of assistive technology, at least partially, to the lack of adequate knowledge and skills of teachers of students with visual impairments in this area (Abner & Lahm, 2002;Edwards & Lewis, 1998;Kapperman et al, 2002;Lee & Vega, 2005;Parker et al, 1990). For example, in the study Edwards and Lewis (1998) conducted in Florida, over half the 113 participating teachers of students with visual impairments admitted that they were not familiar with many of the assistive technology devices that were examined in that study and thus lacked the expertise to teach their students how to use the devices.…”
mentioning
confidence: 99%
“…Few studies have addressed the use of assistive technology by persons who are visually impaired (that is, are blind or have low vision). Many experts have written opinions on the topic; most agree that assistive technology is essential for visually impaired individuals to be full participants in a technological society, and many barriers impede access to equipment and training (Augusto & Schroeder, 1995;Mack, Koenig, & Ashcroft, 1990;Parker et al, 1990;Scadden, 2000). In Lewis and Edwards's (1998) study of the use of assistive technology in Florida, over half the teachers of visually impaired students who participated stated that they would have found preservice courses in assistive technology useful.…”
mentioning
confidence: 99%